Ecologia de Xylocopa (Neoxylocopa) cearensis (Hymenoptera, Anthophoridae) nas dunas litorâneas de Abaeté, Salvador, Bahia - Viana, Blandina F.(Universidade Federal da Bahia Instituto de Biologia Depto de Zoologia); Kleinert, Astrid M. P.(Universidade de São Paulo Instituto de Biociências Depto de Ecologia); Silva, Fabiana O.(Universidade Federal da Bahia Instituto de Biologia Depto de Zoologia) (Iheringia. Série zoologia, 2002)
The study was carried out in a 8.2 ha area in an environmental protection area of tropical sea coastal sand dune with "restinga" vegetation in Salvador, Bahia, northeastern Brazil. A total of 1760 bees of Xylocopa (Neoxylocopa) cearensis Ducke, 1910 were netted during the whole year on flowers of 43 plant species belonging to 26 botanic families. The majority of the individuals (79%) concentrated their foraging activity in five plant species. Individuals foraged all day long being the greatest activity between 8 h and 14 h. Similar proportions of young and old bees were sampled over the year. The density of substrates used for nesting was 4.56/ha. In total, 94% of the nests were found in branches of Agaristha revoluta (Spr.) DC. (Ericaceae). The great occurrence (68.7%) of old perforations indicates that the nests were used twice or more times by bees.